CESifo World Economic Survey November 2010 - Klaus Abberger; Gernot Nerb; Johanna Plenk (CESifo World Economic Survey, 2010)
World Economic Climate: World Economic Climate slightly deteriorated - Economic Expectations: Economic expectations weakened but remain positive - Inflation: Stable price trend expected - Currencies: Euro appears slightly overvalued - Interest Rates: Short-term interest rates expected to rise less than formerly anticipated - Special Topic: Incoterms rules
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies; Special Topic